Study guides

Q: 6x2 plus 32x plus 12-4x-3x2-36

Write your answer...

Submit

Related questions

9+6x2=21

6x2 + 10x = 2x(3x + 5)

6x2=12 2x-28=?

6x2+x-35 = (2x+5)(3x-7)

6x2 + 7x - 5 = (3x + 5)(2x - 1)

(3x+1)(2x+4) = 6x2+4+2x+12x = 6x2+14x+4

6x2-18x+12 = (6x-6)(x-2)

6x2-17x+7 = (2x-1)(3x-7) when factored

(3x - 5x) + (x2 - 6x2) = -2x -5x2 = -x(2 + 5x)

No.

6x2 + 14x -12 = (3x - 2) (2x + 6). There they are.

It is the same as: 3y24x+y26x2 that is if y2 and 6x2 means y2 and 6x2 respectively

(3x+1)(2x+2)

6x2 + 11x + 3 = 6x2 + 9x + 2x + 3 = 3x(2x + 3) + 1(2x + 3) = (2x + 3)(3x + 1)

yes.it is.

One-houndred and thirty five.

The expression may be : 6x2 + 17x + 12 This factors as, 6x2 + 17x + 12 = (3x + 4)(2x + 3) Or, the expression could be : 6x2 - 17x + 12 This factors as, 6x2 - 17x + 12 = (3x - 4)(2x - 3)

6x2 + 64x - 12 = 10 ∴ 6x2 + 64x - 22 = 0 ∴ 3x2 + 32x - 11 = 0 ∴ 3x2 + 33x - x - 11 = 0 ∴ 3x(x + 11) - 1(x + 11) = 0 ∴ (3x - 1)(x + 11) = 0 ∴ x ∈ {1/3, -11}

2x(3x + 5)

(6 × 2) + 3 = 15

2(3x^2 + 6x + 2)

First take out the common factor (4):4(6x2 + 2x + 1)6x2 + 2x + 1 cannot be factored, so 4(6x2 + 2x + 1) is as far as you can get with factoring.

6x2+19x+10 = (2x+5)(3x+2) Length = 2x+5 Width = 3x+2

It is -14.

10